Zakat Fundraising Strategies to Increase the Number of Zakat Muzakki at BAZNAS in Yogyakarta City - Muhammad Fadhil Aziz; Sunu Prasetya Adi (Universitas Negeri Yogyakarta, 2026)
This study aims to examine strategies for increasing the number of zakat contributors through the professionalization of zakat administrators and the digitization of zakat management at the National Zakat Agency (BAZNAS) in Yogyakarta City, in order to address a research gap in previous studies that have focused solely on institutional aspects without simultaneously integrating marketing mix and SWOT analysis. This study employs a qualitative descriptive approach, with informants comprising BAZNAS leadership, zakat collection staff, and zakat contributors, selected through purposive sampling based on their direct involvement in ZIS collection strategies. Data were collected via in-depth interviews, observations, and documentation, and validated through triangulation of sources and methods. The results indicate that digitizing the zakat payment system and increasing transparency in fund management contribute to increased donor loyalty, with the two factors being cyclically interrelated: transparency strengthens trust, while digitization facilitates access and record-keeping. The theoretical contribution of this study is the enrichment of the 7P Marketing Mix and SWOT integration models in the context of digital zakat management, while its practical contribution consists of policy recommendations for BAZNAS to formulate technology-based collection strategies and enhance public trust.